Interdigital electrode water level sensor - Tapaonoi, Titinan; Phukpattaranont, Pornchai; Suntiamorntut, Wannarat; Chetpattananondh, Kanadit (Engineering and Applied Science Research, 2013)
This paper presents the water level sensor fabricated from a printed circuit board. The copper traces of a printedcircuit board as periodic fingers and capacitance between parallel fingers varied according to the water level.The change of capacitance can be measured and converted to a water level by a microcontroller. The outputsignal of a water level from a microcontroller transmitted to a computer or other devices are compatible with theRS-232 standard. The experimental results show that the water level sensor has linear relation with R2 = 0.9992and maximum error is 2.3 %FSO. In addition, this sensor need low energy. Keywords: Interdigital sensors, Water level sensors, Liquid level measurement, Capacitance sensors